Brand media strategy : integrated communications planning in the digital era - Young, Antony, 1964- (New York : Palgrave MacMillan, 2010)
'From YouTube to Facebook to the iPhone, today's media landscape offers more tools and platforms for the savvy marketer than ever before. And with this rapidly evolving technology come powerful ways to track what's working, what's not, and how to get the maximum impact for your brand in a shrinking economy. Media and brand expert Antony Young explores how today's most innovative marketers are integrating the latest media tools into a comprehensive strategy to grow their brands and are getting unprecedented results. He explores: * the future of advertising in traditional media and how to judge the investment's value in today's results-driven marketing world * how to get the maximum impact out of digital media, including online searches, social media, and mobile phones * the importance of employing non-traditional media vehicles, such as marketing PR, branded entertainment, and product placement. This is a must read for every marketer to help increase their brand's exposure while staying on budget'--Provided by publisher.
Includes bibliographical references and index.
Keywords: Branding (Marketing); Internet marketing; Social media